2020
DOI: 10.1080/00220620.2020.1793739
|View full text |Cite
|
Sign up to set email alerts
|

The shock absorbers: school principals and their conflicts in Chile

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it. http://eprints.gla.ac.uk/248774/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In addition, the study has shown that the main contingencies faced by school leaders in Chile revolve around the relationship between actors: assist families, relationship with and among students and resolution of school staff problems. These results are consistent with other studies that have suggested that one of the most demanding tasks for principals is dealing with students' families, even more so in disadvantaged contexts (Vanni et al, 2018;Aravena and Madrid, 2020). It is also consistent with recent studies proving that school leaders dedicate a significant amount of time to their direct relationship with students, a fact that to a certain extent is relativized by the widely held idea that school principals have a solely indirect impact on student learning (Lee et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the study has shown that the main contingencies faced by school leaders in Chile revolve around the relationship between actors: assist families, relationship with and among students and resolution of school staff problems. These results are consistent with other studies that have suggested that one of the most demanding tasks for principals is dealing with students' families, even more so in disadvantaged contexts (Vanni et al, 2018;Aravena and Madrid, 2020). It is also consistent with recent studies proving that school leaders dedicate a significant amount of time to their direct relationship with students, a fact that to a certain extent is relativized by the widely held idea that school principals have a solely indirect impact on student learning (Lee et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…, 2017; Montecinos et al. , 2018; Aravena and Madrid, 2020). This strongly demanding context, which has as one of its components a significant expansion of administrative tasks (Campos et al.…”
Section: Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…School leaders who focus on instructional practices have a greater impact on student learning outcomes and teaching, especially those who focus on teachers who need to improve their performance (Day et al, 2011;Hallinger, Lee, 2015;Hallinger, Wang, 2015;Hattie, 2015). Based on this evidence, Chile has expanded the pedagogic responsibilities and duties of school principals (Aravena, Madrid, 2020;Marfan, Pascual, 2017;OECD, 2016) in line with the explicit guidelines set out in the National Framework for Good School Leadership and Management of 2015 (Ministry of Education, 2015). Specifically, the framework details two leadership dimensions of the role of principals in enhancing teacher professionalism.…”
Section: Introductionmentioning
confidence: 99%